2015
DOI: 10.1002/2014wr016555
|View full text |Cite
|
Sign up to set email alerts
|

The role of stratification on lakes' thermal response: The case of Lake Superior

Abstract: During the last several decades, the Great Lakes region has been experiencing a significant rise in temperatures, with the extraordinary summer warming that affected Lake Superior in 1998 as an example of the marked response of the lake to increasingly warmer atmospheric conditions. In this work, we combine the analysis of this exceptional event with some synthetic scenarios, to achieve a deeper understanding of the main processes driving the thermal dynamics of surface water temperature in Lake Superior. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
119
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(124 citation statements)
references
References 45 publications
5
119
0
Order By: Relevance
“…This is supported by a high correlation between LSTs in March and July according to both GLSEA2 ( r = 0.77) and the CTRL simulation ( r = 0.68) during 1995–2012. In contrast, Piccolroaz et al () found that winter conditions explain only 22% of the July warming from 1997 to 1998. The extra heat accumulated during the antecedent winter supports an earlier lake stratification in 1998, compared to 1997.…”
Section: Drivers Of Increased Lst: Antecedent Winter Lake Conditions mentioning
confidence: 90%
See 1 more Smart Citation
“…This is supported by a high correlation between LSTs in March and July according to both GLSEA2 ( r = 0.77) and the CTRL simulation ( r = 0.68) during 1995–2012. In contrast, Piccolroaz et al () found that winter conditions explain only 22% of the July warming from 1997 to 1998. The extra heat accumulated during the antecedent winter supports an earlier lake stratification in 1998, compared to 1997.…”
Section: Drivers Of Increased Lst: Antecedent Winter Lake Conditions mentioning
confidence: 90%
“…Potential drivers of global lake warming may include changes in large‐scale meteorological forcings (e.g., air temperature and solar radiation), internal lake processes (e.g., changes in lake ice cover and timing of stratification), and lake eutrophication in response to land use and resulting sedimentation (Austin and Colman ; Adrian et al ; Wang et al ; Wild ; Fink et al ; Dokulil et al ; Piccolroaz et al ). The warming of European lakes has been attributed to increases in both air temperature and incoming solar radiation (Arvola et al ; Fink et al ).…”
mentioning
confidence: 99%
“…6). Piccolroaz et al (2015) showed that an increase in lake stability and earlier onset of stratification causes warming of surface waters due to the smaller volume undergoing warming and diminished heat transfer to the hypolimnion. The lake model used here showed an increase in stratification strength and a lengthening of the stratified period in both lakes (Table 5; Fig.…”
Section: Lakesmentioning
confidence: 99%
“…Climate change has been shown to exert a strong influence on thermal dynamics of waters worldwide (Fink, Schmid, Wahl, Wolf, & Wuest, ; Jansen ; O'Reilly & Sharma ; Piccolroaz, Toffolon, & Majone, ; Piccolroaz et al, ; Wood, Wherry, Piccolroaz, & Girdner, ). Kraemer, Anneville, and Chandra () used a 1D hydrodynamic model to investigate the impacts of atmospheric warming on the thermal structure of Lake Geneva.…”
Section: Introductionmentioning
confidence: 99%